Preemptive pregabalin for postoperative analgesia during minimally invasive hysterectomy: a systematic review and meta-analysis of randomized controlled trials - Ahmed Abu-Zaid; Osama Alomar; Nora F AlNaim; Fatimah Shakir Abualsaud; Mohammed Ziad Jamjoom; Latifa F AlNaim; Abdullah AMA Almubarki; Saeed Baradwan; Saud Abdullah Saud Aboudi; Faisal Khalid Idris; Meshael Fodaneel; Ismail A Al-Badawi; et al. (Korean Society of Obstetrics and Gynecology, 2022)
We aimed to perform a systematic review and meta-analysis of all randomized placebo-controlled trials (RCTs) that examined the analgesic benefits of preemptive pregabalin among patients undergoing minimally invasive hysterectomy. Five major databases were systematically screened from inception until August 29, 2021 Relevant studies were evaluated for risk of bias. Endpoints were analyzed using the random-effects model and pooled as the mean difference or risk ratio with a 95% confidence interval. Four studies with seven treatment arms met the inclusion criteria. The total sample size was 304 patients: 193 and 111 patients were allocated to the pregabalin and placebo groups, respectively. Overall, the included studies revealed a low risk of bias. The summary results revealed that the mean postoperative pain scores at rest were significantly lower in the pregabalin group than in the control group at 0, 2, 4, 6, 12, and 24 hours. Moreover, the mean postoperative pain scores on movement/coughing were significantly lower in the pregabalin group than in the control group at 12 and 24 hours. The rate of patients who were opioid-free postoperatively was significantly higher in the pregabalin group than in the control group. There was no significant difference between the groups in terms of the mean postoperative time to first rescue analgesic and the rates of adverse events. Compared with placebo, preemptive pregabalin was largely safe, and was correlated with superior analgesic effects in terms of lower postoperative pain scores and higher opioid-sparing effects. Additional RCTs are needed to confirm these findings.